PERHITUNGAN NILAI GARANSI MINIMUM MANFAAT KEMATIAN PADA ASURANSI UNIT-LINK - DEWI, NI KOMANG AYU SEDANA; WIDANA, I NYOMAN; HARINI, LUH PUTU IDA (E-Jurnal Matematika, 2018)
The guarantee minimum on unit-linked insurance applies only to the most extreme situations of very bad rate of return on the fund’s policyholders. One of the investment guarantees commonly used in unit-link is guaranteed minimum death benefit (GMDB). The final value under unit-linked insurance contracts can be expressed in terms of options that can be calculated using the Black-Scholes-Merton method. The purpose of this study is to determine the effect of age to the guarantee minimum value calculated using the Black-Scholes-Merton method. The calculation of GMDB value based on case simulation in this study resulted that the increasing age of the insured the greater the minimum guarantee value to be obtained.